A metacognitive support environment for novice programmer using semantic web / Siti Nurulain Mohd Rum - Siti Nurulain, Mohd Rum (2016)

(untitled)
It is has been acknowledged that acquiring programming knowledge is very challenging for someone that is very new to programming. Computer programming education for both teaching and learning is generally known to be difficult as it requires a higher level of knowledge and practice ability rather than theory alone. The skill of metacognition, which is apparently lacking among novices is required for the knowledge of “When and why” in computer programming practice to manage cognitive skills efficiently and facilitate the learning process as well as the transfer of knowledge. This study aims to identify the methods of supporting novice programmers in learning computer programming metacognitively. Several steps are taken in realizing this. Firstly, a survey using Metacognitive Awareness Inventory (MAI) is performed to investigate the effect of metacognition on the performance in respect of the Computer Programming subject. The respondents that participated in this study are the undergraduate students with a computer science background from several universities in Malaysia. The result indicates that metacognition has a positive effect on students’ achievement in the Computer Programming Subject at university. The results also revealed that i) problem-solving is the type of strategy that usually works for them to understand programming, ii) novices need a support environment to assist them to monitor and evaluate their knowledge in learning programming, and iii) the majority of the novices are motived to use a support environment if it provides criteria like learnability, helpfulness and affect. Secondly, interview sessions are conducted with expert lectures in Computer Programming at the Faculty of Computer and Mathematical Science, University Teknologi MARA, Shah Alam. The objective of the interview was to investigate the awareness and the implementation of metacognition in teaching Introductory Computer Programming at the University. The findings of the survey show that i) expert lecturers employed metacognition in teaching, and teaching metacognition iv skills for improving student’s learning process and ii) expert lecturers recognize the role of metacognition as one of an important learning success factors of the computer programming subject that must be done before, during and after instruction. Semantic Web is an ideal technology for the development of the proposed system that facilitates the process of differentiating the ambiguity lies between cognitive and metacognitive elements. Thirdly, a usability test is conducted using the Software Usability Measurement Inventory (SUMI) to determine the user’s perception towards the MSSNP in terms of the affect, efficiency, control, helpfulness and learn-ability. The results of the usability test show that the MSSNP is an ideal system to support the metacognitive activities for learning Introductory Computer Programming. Finally, an experimental study is conducted, which comprise an empirical evaluation of observations on student interaction with the MSSNP. It concentrates primarily on the observation of metacognitive changes as well as changes in performance. The subjects are categorized into two groups (experimental and control) in which each one are associated with different conditions. The results show that students in the experimental group developed more favorably compared to those in the control group with respect to metacognition behavior and performance.